2020
DOI: 10.1108/tr-01-2019-0032
|View full text |Cite
|
Sign up to set email alerts
|

Senior tourism – a scientometric review (1998-2017)

Abstract: Purpose This study aims to identify intellectual structures, emerging trends and future research opportunities via a bibliometric analysis of senior tourism research from 1998 until 2017. Design/methodology/approach A detailed search of 700 core articles and 7,221 citations collated from Web-of-Science and Scopus was implemented and analyzed through CiteSpace. Findings The results reveal a slow increase in the amount of research, with six main areas of research. The most cited articles are mainly older. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…We used keyword analysis in this study because this type of analysis and its synchronization makes it possible to draw the subjective structure of a field and its changes for a period of time (Ding et al, 2001). In addition, the use of keywords in different periods helps to identify the research process (Pestana et al, 2020). Therefore, we analyzed all the keywords to examine their relationship with the research flow of the "Tourism Distribution…”
Section: Research Themesmentioning
confidence: 99%
See 2 more Smart Citations
“…We used keyword analysis in this study because this type of analysis and its synchronization makes it possible to draw the subjective structure of a field and its changes for a period of time (Ding et al, 2001). In addition, the use of keywords in different periods helps to identify the research process (Pestana et al, 2020). Therefore, we analyzed all the keywords to examine their relationship with the research flow of the "Tourism Distribution…”
Section: Research Themesmentioning
confidence: 99%
“…Also functionally, the useful use of channels of distribution depends on an adequate understanding of the evolution of these channels in the tourism industry (Kracht & Wang, 2010). Bibliometrics is a tool for analyzing how disciplines have evolved based on intellectual structure, social structure, and conceptual structure (Koseoglu et al, 2016) which is rarely used in tourism research and has potential if applied (Pestana et al, 2020). Therefore, this study uses bibliometrics in order to examine the evolution of tourism distribution channels as one of the most important subfields of tourism that has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many systematic review studies have been conducted on hospitality and tourism to understand the progress of research topics [9,17,[55][56][57][58]. Previous studies have examined the evolution of citations within a particular research topic [58,59] or identified individual research papers that received high citations [56]. More specifically, some studies have focused on bibliometrics-based studies in the field of hospitality and tourism [59][60][61].…”
Section: Maturity Of Research Topicsmentioning
confidence: 99%
“…Generally, bibliometric methods complement traditional subjective literature reviews through quantitative bibliographic data (Small, 2003;Zupic and Cater, 2015). In the context of tourism, bibliometric analysis has been widely used for the assessment and evolution of journals (Leong et al, 2021), the evolution analysis of various forms of tourism (Pestana et al, 2020), amongst others. Bibliometric analysis generally comprises five main methods: citation, bibliographic coupling, keyword co-word, co-citation and co-author (Cobo et al, 2011;Zupic and Cater, 2015).…”
Section: Bibliometric Analysismentioning
confidence: 99%